A Qualitative Study of Factors Influencing the Onset of Hookah Smoking among Iranian Men with Turkmen Ethnicity - Shirin Shahbazi Sighaldeh; Fatemeh Zarghami; Abdurrahman Charkazi; Reza Negarandeh (Springer, 2019)
Introduction: Hookah smoking has grown considerably among Iranian Turkmen in the past two decades. The reasons for this increase in the consumption of hookah are unclear. Therefore, this study was conducted with the aim of determining the factors related to the start of hookah smoking in men with Turkmen ethnicity. Methods: This qualitative study was conducted between February 2018 and June 2018 in Turkmen cities of Golestan provinces in Iran. The study participants included 26 male Turkmen water pipe smokers with various ages, occupation, and education level. Study data were collected through semi-structured individual interview and the results were analyzed in August 2018 by content analysis. Data management was done by software, MAXQDA version 10. Results: In this study, 26 hookah smoker men with the age range of 20-45 years were interviewed. The age of the participants at the time of starting hookah consumption varied from 14 to 25 years. On the basis of qualitative data, the reasons for the start of hookah smoking in male Turkmen were classified into three main categories: (1) individual (curiosity and sense of adulthood, fewer perceived risks compared with other substances and hookah's sensory attractions); (2) interpersonal (hookah-smoking friends and consumption of hookah by family members); and (3) societal (blaming unemployed people in small neighborhoods, cultural influence, more social acceptance compared with other substances, and easy access to hookah). Conclusion: Individual, interpersonal, and societal factors play important role in the start of hookah smoking among male Turkmens. Developing health policies based on the above factors can be effective in adopting hookah prevention and control strategies. Moreover, future studies could be developed with the goal of discovering ways to solve the problem of unemployment and plan for developing recreational activities in this area to prevent initiation of hookah smoking especially among youth.